SETTLEMENT ABILITY OF PEARL OYSTER (Pinctada maxima) LARVAE AT DIFFERENT POSITIONS AND DEPTHS COLLECTORS - Mat Sardi Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
One of the success  factor in the cultivation of pearl oysters (Pinctada maxima) within laboratory scale of  is the  ability of the larvae to settle on  the collector. Stocking collectors which are not on time with an irregular position could cause a decline in seed production. The research was conducted from 25 July to 27August 2011 at Laboratory of Marine Bio-industry Technical Implementatation Unit,  Research Centre for Oceanography, Indonesian Institute of Sciences, Lombok, West Nusa Tenggara (NTB). The aim of the study was to observe the attachment of larvae at different position and depth. Analysis of variance showed that larvae settlement was influenced  by  depth instead of position and the interaction between them. Real Honest Different Test showed that in the 20 cm depth was significantly different from  60 cm and 100 cm in number of larvae attached  on the collector. The highest survival rate was in 20 cm depth with 68,98% (516 larvae) while in 60 cm was 17,11% (128 larvae) and 100 cm (9,22% (69 larvae), and the others were attached on the wall of  the tank 4,68% (35 larvae). Keywords: settlement ability of pearl oyster’s larvae (Pinctada maxima), collector, depth